Listy Augusta Cieszkowskiego juniora do Mariana Zdziechowskiego z lat 1907–1913 - Marlęga, Monika (Colloquia Litteraria, 2013)
August Cieszkowski junior’s letters to Marian Zdziechowski from the years 1907–1913 Marian Zdziechowski has long been a big absentee in Polish humanities, even though he played a significant role in the intellectual life of the half of the century rich in cultural and political turns. His sensitivity and sensitiveness to the novelties of the intellectual trends of the epoch let him diagnose the contemporary human condition fairly quickly. They also allowed for him to accurately point to the necessities of the moment, both within the historical and religious fields. Zdziechowski had a particular ability to openly look at man, religion, history and philosophy, hence the possibility to acquaint oneself even with just a small part of his correspondence may prove extremely valuable. Cieszkowski junior’s letters to Marian Zdziechowski from 1907– –1913, that are presented here, are the source of information on Zdziechowski’s interest in Polish Romanticism and the bases and inspirations of Polish philosophy of the period. These letters bring the addressee closer to the reader, which is characteristic of correspondence in general. The reading of these letters makes us direct witnesses to the views expressed in them and discussions relevant to the letters’ recipient. The issues addressed in the letters concern mostly the origins of Polish messianism, Towianism and its possible influence on Zygmunt Krasiński and the philosophy of August Cieszkowski, the question of the Slavic Idea and the way of perceiving Russia.